The Legal Protection for Concurrent Creditors in the Context of Enforcing Bankruptcy Cases (Jurnal Daulat Hukum, 2022)
This study aims to find out and find out about the form of legal protection regulations given to concurrent creditors. This study uses a normative juridical approach. Basically, Act No. 37 of 2004 has provided legal protection to concurrent creditors against actions by bankrupt debtors, separatist creditors, curators and supervisory judges, namely: (a) legal protection for creditors concurrent against the bankrupt debtor: confiscation of collateral (Article 10), immediate decision [Article 8 paragraph (7) and Article 16)], silence [Article 24, Article 25, Article 27, Article 34, Article 40 paragraph (1 ), and Article 97), Actio pauliana (Article 30 and Article 41 - Article 47), forced corporal (Article 93 - Article 96), sealing of bankruptcy assets (Article 99), objections to requests for rehabilitation (Articles 218 and Article 220), and supervision of debtor communications (Article 105); legal protection for concurrent creditors against separatist creditors.